Dose Trifolium pratense L. Protect against Development of Fatty Streak in Coronary Arteries? - S Asgari; J Moshtaghian; GA Naderi; Z Fatahi; M Hosseini; GR Dashti; Sh Adibi (Institue of Medicinal Plants, ACECR, 2007)
Background: Phytoestrogens with a biological activity like estradiol are naturally found in many plants. Objective: This study was designed to investigate the effect of red clover (RC), a phytoestrogen-rich member of the legume family (Trifolium pratense L.) on the development of atherosclerosis in male hyperlipidemic rabbits. Method: Twenty rabbits were semi-randomly distributed into four groups of five each. Two groups received either normal diet or normal diet supplemented with RC. Two other groups received similar diets to both of which 1% cholesterol was added. Results: Dietary use of RC in hyperlipidemic rabbits significantly decreased C-reactive protein (CRP), triglyceride (TG), total cholesterol and LDL-cholesterol (LDL-C) whereas, HDL - cholesterol (HDL-C) was significantly increased in those animals (p<0.05). Fatty streak formation was also significantly lower in aorta and left and right coronary arteries in the same animals due to use of dietary RC supplementation. Conclusion: These findings suggest that dietary RC may reduce cardiovascular risk factors.